Sistem Rekomendasi Buku di Perpustakaan Berbasis User-Based Collaborative Filtering - Missi Hikmatyar; Ruuhwan Ruuhwan; Zery Hendra (STMIK IKMI Cirebon, 2019)
A library has a Book Search System, both search books by title, author, publisher and book subject. Book search results displayed by the system, sometimes it makes users (library members) find it difficult to choose books that match their profile. For that we need a system that can provide recommendations in the book search process to provide recommendations systematically based on previous user searches. This study aims to produce a book search recommendation. Recommendation system aims to reduce errors in getting the reference books needed. The information that comes out of the search process is right on target with user needs so that it can streamline time in searching for books. Book search recommendation system uses a user-based collaborative filtering method based on the similarity of one member to another member based on the lending pattern which is grouped based on the subject of the book being sought. This system will display the results of book search recommendations by ranking ranking from highest to lowest and provide book title solutions to users according to their profile. The development of the book search recommendation system uses the System Development life cycle (SDLC) method. Book recommendation system based on user-based collaborative filtering depends on the search for books by users by looking at the similarities of search by users.